2014
DOI: 10.4067/s0718-381x2014000200022
|View full text |Cite
|
Sign up to set email alerts
|

The Expression of Nitric Oxide in the Gingival Tissue in Subjects with Periodontitis and Chronic Pain

Abstract: Periodontal disease (PD) is a chronic infection that may have local and systemic rebound. Although a series of inflammatory mediators are involved in PD, the mechanisms involved in chronic craniofacial pain associated with it require elucidation. The aim of this study was to evaluate the immunoreactivity of substance P (SP), neuronal (nNOS) and inducible (iNOS) nitric oxide synthases in gingival samples of patients with severe PD with and without chronic craniofacial pain. Gingival specimens were obtained duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
3

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 20 publications
0
4
0
3
Order By: Relevance
“…At the end of the selection process, 11 articles were obtained. Nine studies observed the expression of NOS and/or NO through the clinical and laboratory studies 7,14,[16][17][18][19][20][21][22] . The methodological parameters used to evaluate the periodontal condition were the following: PI = plaque index (%), CEJ = cementoenamel junction, GI = gingival index, BP= bleeding on probing (%), CAL = clinical attachment level (mm), and probing depth .About laboratory studies, the incisional gingival biopsies and laboratory tests by immunohistochemistry were described.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…At the end of the selection process, 11 articles were obtained. Nine studies observed the expression of NOS and/or NO through the clinical and laboratory studies 7,14,[16][17][18][19][20][21][22] . The methodological parameters used to evaluate the periodontal condition were the following: PI = plaque index (%), CEJ = cementoenamel junction, GI = gingival index, BP= bleeding on probing (%), CAL = clinical attachment level (mm), and probing depth .About laboratory studies, the incisional gingival biopsies and laboratory tests by immunohistochemistry were described.…”
Section: Resultsmentioning
confidence: 99%
“…Among the 11 articles included in this systematic review, 5 studies looked at the expression of NOS and/or NO and their metabolites in PD 3,7,[19][20][21] and other 5 studies quantified the expression of NOS, NO and metabolites in OP 14,17,18,22,24 . Only one article revealed the expression of NOS simultaneously in patients with and OP 16 .…”
Section: Resultsmentioning
confidence: 99%
“…A doença periodontal (DP) é frequente na população mundial e embora tenha tratamento conhecido e eficaz nem sempre é reconhecida, uma vez que seus sinais e sintomas são considerados irrelevantes pelos pacientes. Savioli et al, 2004;Savioli et al, 2010;Savioli et al, 2012;Siqueira et al, 2010;Fernandes et al, 2007;Fabri et al, 2009;Fabri et al, 2014a;Fabri et al, 2014b;Fabri et al, 2014c;Rolim et al, 2014 . Em outro estudo brasileiro contendo uma amostra maior de pacientes adultos e idosos foi verificado que a prevalência de dor no segmento orofacial foi de 55,5%.…”
Section: Revisão De Literaturaunclassified
“…Não houve diferenças para os demais parâmetros (Tabela 5). (Fabri et al, 2009;Fabri et al, 2014b). Entretanto os resultados do presente estudo devem ser interpretados com cautela e mais estudos serão necessários para avaliar a relação DP, número de dentes afetados e nocicepção.…”
Section: Comportamento De Ansiedadeunclassified
See 1 more Smart Citation